2021
DOI: 10.1590/1806-93042021000200007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with unplanned pregnancy in a Brazilian capital in the Northeast

Abstract: Objectives: to analyze the prevalence and factors associated with unplanned pregnancy in a Brazilian capital in the Northeast. Methods: a cross-sectional study nested to a hospital birth cohort with a probable sample of 5,110 puerperal women. Associated factors were analyzed using a hierarchical theoretical model in three levels: distal (women’s socioeconomic and demographic characteristics), intermediate (reproductive characteristics, maternal habits and BMI), and proximal level (partner's characteristics). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
5
0
7
Order By: Relevance
“…Black mothers also showed a higher PR for not planning the pregnancy, confirming a similar finding in other studies 9,15,24,28,29 . Besides the factors already mentioned, Black mothers struggle more in accessing health services that are often insufficient and have inadequate quality [28][29][30][31] .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Black mothers also showed a higher PR for not planning the pregnancy, confirming a similar finding in other studies 9,15,24,28,29 . Besides the factors already mentioned, Black mothers struggle more in accessing health services that are often insufficient and have inadequate quality [28][29][30][31] .…”
Section: Discussionsupporting
confidence: 90%
“…The mean prevalence of 63.3% of non-planning observed in these surveys is similar to that observed in the baseline of the 1993 Pelotas cohort (62.7%), slightly lower than in 2004 (65.9%), but higher than the 2015 rate (52.2%) 10 . In São Luís, Maranhão, this prevalence reached 68.1% in 2010 24 , while it was 53.8% in Ribeirão Preto, São Paulo 25 . In Brazil, a hospital-based study conducted between 2011-12 found a prevalence of non-pregnancy planning of 55.4% 9 , while a survey conducted in 2020 in eight university hospitals identified 67.5% 12 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Modelo lógico do projeto CRIA (Cultivate and Raise Infancy Awareness) ao uso de tabaco, álcool e outras drogas (Pereira et al, 2010). A dificuldade de acesso aos métodos contraceptivos por falta de educação sexual (Costa et al, 2021;Prietsch et al, 2011). O contágio de infecções sexualmente transmissíveis (Santos et al, 2020).…”
Section: /16unclassified